The role of MMP-14 in ovarian cancer: a systematic review - M. Caroline Vos; Anneke A. M. van der Wurff; Toin H. van Kuppevelt; Leon F. A. G. Massuger (Journal of Ovarian Research, 2021)
Abstract Aim In order to evaluate the role of MMP-14 in ovarian cancer, a systematic review was conducted. Methods In March 2020, a search in Pubmed was performed with MMP-14 and ovarian cancer as search terms. After exclusion of the references not on MMP-14 or ovarian cancer or not in English, the studies found were classified into two categories: basic research and clinicopathological research. Results In total, 94 references were found of which 33 were excluded. Two additional articles were found in the reference lists of the included studies. Based on the full texts, another 4 were excluded. Eventually, 59 studies were included in the review, 32 on basic research and 19 on clinicopathological research. 8 studies fell in both categories. The basic research studies show that MMP-14 plays an important role in ovarian cancer in the processes of proliferation, invasion, angiogenesis and metastasis. In clinocopathological research, MMP-14 expression is found in most tumours with characteristics of poor prognosis but this immunohistochemical MMP-14 determination does not seem to be an independent predictor of prognosis. Conclusions From this systematic review of the literature concerning MMP-14 in ovarian cancer it becomes clear that MMP-14 plays various important roles in the pathophysiology of ovarian cancer. The exact translation of these roles in the pathophysiology to the importance of MMP-14 in clinicopathological research in ovarian cancer and possible therapeutic role of anti-MMP-14 agents needs further elucidation.